3D interaction diagrams for symmetrically reinforced concrete square sections with various reinforcement ratios. (1st July 2022) - Doulgeroglou, Androniki-Anna; Kotronis, Panagiotis; Sciarra, Giulio; Bouillon, Catherine
Abstract: 3D interactions diagrams for symmetrically Reinforced Concrete (RC) square sections with various reinforcement ratios are constructed using 3D non-linear finite element simulations. The interaction diagrams are expressed in terms of generalized forces (axial force, bending moment and shear force) and allow to identify two characteristic states: the first characteristic state corresponds to the elastic limit of the reinforcement bars (while concrete exhibits a non-linear behavior) and the second characteristic state to the peak values of the generalized forces generalized displacements curves. Firstly, 3D non-linear finite element simulations of RC cantilever-type columns are presented and validated with experimental results. Numerical interaction envelopes are then derived and analytical convex expressions are provided. Finally, a comparison with existing interaction diagrams from the literature is proposed. Highlights: 3D interaction diagrams for Reinforced Concrete sections. 3D nonlinear finite element simulations. Identification of two characteristic states. Derivation of numerical interaction envelopes. Analytical convex expressions.